RESIDENTS’ PERCEPTIONS OF TOURISM IN RELATION TO THEIR PERSONAL WELL-BEING - Soldic Frleta, Daniela; Durkin Badurina, Jelena; Kaliterna Lipovcan, Ljiljana (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
This study examines the relationships between residents’ perceptions of tourism and their overall personal well-being. In addition, the study aims to find out what differences exist in the perception of personal well-being and the impact of tourism between residents who provide private accommodation for tourists and those who do not. A questionnaire survey is conducted to collect data from residents of the city of Rijeka, Croatia, and 556 usable questionnaires are generated. The analysis of residents’ perceptions is done separately for those who provide private accommodation to tourists and those who do not. Respondents in both groups reported relatively high levels of personal well-being. However, those who provide private accommodations for tourists are more satisfied with several areas of life. The results show that overall satisfaction with living conditions, perceived negative impacts of tourism, age, and whether or not residents offer accommodation to tourists are significant predictors of their personal well-being. This study aims to add to the literature on the well-being of residents of tourist destinations by examining the relationship between their perceived well-being and their perceptions of various impacts of tourism in their community.